2022
DOI: 10.1021/acsanm.2c03372
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide-Based Field Effect Transistor Biosensors for High-Sensitivity miRNA21 Detection

Abstract: Breast cancer has been ranked the first malignant tumor in women, and with the incidence of it increasing all over the world, early screening can effectively reduce mortality and improve the cure rate. MiRNAs, as potential biomarkers, play an important role in the early diagnosis and prognosis monitoring of breast cancer. However, since miRNAs, with low concentration, are the matrix in serum or plasma, accurately detecting miRNAs without a label in serum or plasma is challenging. Herein, we proposed a biosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…[78,79] Among others, those based on electrochemical and/or optical sensing platforms coupled with suitably designed microfluidics seem to be very promising to this end. Biosensing platforms relying on screen-printed electrodes, field effect transistor (FET), [80,81] surface plasmon resonance (SPR) [75,82,83] or surface-enhanced Raman scattering (SERS) [84][85][86][87] may offer the advantage of an unprecedented high sensitivity and fast detection times. Moreover, they can also be integrated with a second "dummy" sensing platform as the reference to provide a more accurate differential measurement.…”
Section: Discussionmentioning
confidence: 99%
“…[78,79] Among others, those based on electrochemical and/or optical sensing platforms coupled with suitably designed microfluidics seem to be very promising to this end. Biosensing platforms relying on screen-printed electrodes, field effect transistor (FET), [80,81] surface plasmon resonance (SPR) [75,82,83] or surface-enhanced Raman scattering (SERS) [84][85][86][87] may offer the advantage of an unprecedented high sensitivity and fast detection times. Moreover, they can also be integrated with a second "dummy" sensing platform as the reference to provide a more accurate differential measurement.…”
Section: Discussionmentioning
confidence: 99%
“…A high-sensitivity, low-cost, and noninvasive biosensor to directly detect miRNA21 (a potential biomarker for predicting chronic lung disease in premature infants) in the plasma of breast cancer patients based on p-DNA-rGO-FET with 1fM of LOD was developed by Cai et al, 224 as shown in Figure 13a. On the other hand, Rahman et al 225 reported an ultrasensitive label-free biosensor for detecting gastric-cancer-related PIK3CA gene of ctDNA in peripheral blood, as shown in Figure 13b.…”
Section: Carbon Dots (Cds)mentioning
confidence: 99%
“…(a) rGO-based field-effect-transistor biosensors for detecting miRNA21 related to breast cancer. Reprinted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Carbon-based Nanomaterials (Cbns)mentioning
confidence: 99%
“…Second, the nucleic acid biosensors are efficient for early diagnosis of genetic diseases, e.g., miRNA21 (breast cancer), as well as mass screening of coronavirus disease 2019. Indeed, the DNA aptamer modified graphene transistor promotes the detection of viruses in several minutes for self-test at home . Recently, CRISPR technique was integrated with transistor platform for breaking the detection limit to attomole per liter level …”
Section: Electronic Tongue For Tastementioning
confidence: 99%